2001
DOI: 10.1097/00006534-200108000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Transforming Growth Factor-β Receptors I and II and Activation of Smad 3 in Keloid Fibroblasts

Abstract: Keloids represent a dysregulated response to cutaneous wounding that results in an excessive deposition of extracellular matrix, especially collagen. However, the molecular mechanisms regulating this pathologic collagen deposition still remain to be elucidated. A previous study by this group demonstrated that transforming growth factor (TGF)-beta1 and -beta2 ligands were expressed at greater levels in keloid fibroblasts when compared with normal human dermal fibroblasts (NHDFs), suggesting that TGF-beta may pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
132
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 31 publications
8
132
1
1
Order By: Relevance
“…Similar ligand-independent SMAD activation has been described in hepatic stellate cells derived from fibrotic livers (56) and in dermal fibroblasts derived from keloid lesions (57). Constitutive SMAD activation is therefore likely to contribute to the profibrotic phenotype of scleroderma fibroblasts.…”
Section: Discussionsupporting
confidence: 57%
“…Similar ligand-independent SMAD activation has been described in hepatic stellate cells derived from fibrotic livers (56) and in dermal fibroblasts derived from keloid lesions (57). Constitutive SMAD activation is therefore likely to contribute to the profibrotic phenotype of scleroderma fibroblasts.…”
Section: Discussionsupporting
confidence: 57%
“…Bettinger et al also found a significant increase in the response rate to TGF-ß in KFs, with an increase in fibroblast proliferation and collagen synthesis (15). Increased rates of proliferation and collagen synthesis suggest an altered response of KFs to this cytokine, which might reflect a modification in the regulatory pathway that occurs at the receptor level or during intracellular transduction (4,9). According to the literature, TGF-ß1 and -ß2 mRNA expression was found to be higher in KFs than in NFs or hypertrophic scar fibroblasts, whereas TGF-ß3 mRNA expression was significantly lower (3,11,25).…”
Section: Discussionmentioning
confidence: 98%
“…They grow invasively into the surrounding healthy skin and are not confined to the border of the initial wound. They seldom show a tendency to regress spontaneously (2)(3)(4). The prevalence between the male and female gender is equally distributed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely accepted that the dysregulation of the TGF-β/Smad pathway plays a key role in hypertrophic or keloid scar formation in human skin tissues. A number of studies have clearly demonstrated that the increased expression of TGF-β receptors (types I and II) and the increased phosphorylation of Smad3 in keloid fibroblasts compared to normal HSFs, as well as the suppression of the TGF-β1/Smad pathway by certain chemicals such as curcumin, may exert chemopreventive effects, thus preventing keloid formation (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%